Impact of Thermal Treatment on the Surface of Na0.5Bi0.5TiO3-Based Ceramics - Liga Bikse; Marija Dunce; Eriks Birks; Karlis Kundzins; Otto Freimanis; Maris Livins; Jevgenijs Gabrusenoks; Andris Sternberg (Crystals, 2021)
Thermal etching is a widely accepted surface treatment method for studying microstructure in Na0.5Bi0.5TiO3-based compositions. Surprisingly, besides the flat pattern of grains (suitable for evaluating ceramics’ microstructure), images illustrating well-expressed relief and even microstructure consisting of partly bonded cubic-shaped grains are also found among the micrographs presented in various publications. The present paper shows that this different surface character in Eu-modified Na0.5Bi0.5TiO3 can be obtained through thermal treatment across a wide range of temperatures. At higher temperatures, remarkable growth of cubic-shaped grains on the surface is observed. This growth affects the grain size distribution on the surface more than it does within the bulk of a sample. Such micrographs cannot be used to characterise the microstructure of dense ceramics. Intensive growth of TiO2 inclusions at high thermal treatment temperatures is also observed, revealing substantial evaporation of Bi and Na from the surface of a ceramic sample, but not from its core part.